Drowning or Waving? Citizenship, Multiculturalism and Islam in Malaysia - Drakeley, Steven (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2008)
This article examines some intriguing shifts in Islamic thinking on questions around citizenship and multiculturalism that have emerged in the Malaysian context in recent years. It does so in the light of the March 2008 election results and other recent political developments, notably the rise of Anwar Ibrahimâs PKR, and considers the implications for Malaysia. Of particular focus is the novel Islam Hadhari concept articulated by UMNO leader Prime Minister Badawi and the relatively doctrinaire Islamic state ideas of Islamist PAS. The article argues that these shifts in Islamic thinking are largely propelled by politics. Partly they are propelled by the logic, in a narrow political sense, imposed by the particular political circumstances that confront these Muslim-based political parties in Malaysiaâs multi-ethnic, multi-religious setting. Partly the impetus is derived from growing general concerns in Malaysia that a new and more stable and enduring settlement of the issues associated with the countryâs notorious horizontal divisions must be found if Malaysia is to avoid a disastrous plunge into communal conflict or tyranny.